The productivity spillovers of foreign direct investment in China: a computable general equilibrium model - Deng, Ziliang (2009)
One of the most important aspects of foreign direct investment (FDI) is that it embodies advanced technologies and business practices which can spill over to domestic firms via various channels, e.g. labour mobility, input-output linkages, export of multinational affiliates, demonstration and competition.